Evaluation of Peripapillary Nerve Fiber Layer after Dexamethasone Implantation (Ozurdex) in Branch Retinal Vein Occlusions - Muhammed Nurullah Bulut; Yusuf Özertürk; Ümit Çallı; Güzide Akçay; Ulviye Kıvrak; Kezban Bulut (Journal of Ophthalmology)
Purpose. To evaluate the peripapillary retinal nerve fiber layer (RNFL) thicknesses of patients treated with intravitreal Ozurdex implant due to branch retinal vein occlusion (BRVO) related macular edema (ME). Methods. Thirty-three eyes of 33 patients treated with Ozurdex implant due to ME associated with BRVO were included in the study. Ophthalmic examinations including determination of best corrected visual acuity (BCVA), measurement of intraocular pressure (IOP), and central macular thickness (CMT) and peripapillary RNFL assessment with optical coherence tomography (OCT) were performed before the injection of Ozurdex implant and during the 6-month follow-up period after the injection. Results. The mean age was 55.2 ± 7.4 (range: 40–68) years. The BCVAs were significantly increased and CMTs were significantly decreased at month 3 and month 6 visits compared to baseline values. The mean IOP was significantly increased from baseline at day 1, week 1, and month 1 visits (p1=0.008, p2=0.018, and p3=0.022, resp.). The average and inferior quadrant peripapillary RNFL thicknesses were significantly reduced at month 6 control visit compared to baseline values (both p<0.001). Conclusions. Ozurdex implant improved the BCVA and reduced the CMT in the eyes with RVO related ME. However, IOP elevations occurred within the first month after the injection and the average and inferior quadrant RNFL thinning was found six months after the injection. Further controlled studies are warranted.